OP0191 All-cause mortality and cardiovascular death in hydroxychloroquine users in rheumatoid arthritis patients – a population based danish cohort study. (12th June 2018) - Soeltoft, K.; Hallas, J.; Wasko, M.C.M.; Pedersen, A.B.; Ulrichsen, S.P.; Ellingsen, T.
Abstract : Background: Rheumatoid arthritis (RA) is associated with a marked increase in cardiovascular comorbidity and mortality(. 1 The increased risk is present from the earliest stages of the disease and evidence suggests an overlap in the pathogenic features leading to RA and atherosclerosis. Hydroxychloroquine (HCQ) is used to treat RA in combination with methotrexate and has been associated with decreased risk of type II diabetes and dyslipidaemia among RA patients. Also HCQ has improved survival rates when used to treat other inflammatory diseases, e.g. systemic lupus erythematosus(. 1 The evidence regarding RA patients is scarce. Objectives: We wish to examine whether HCQ would affect the incidence rates of cardiovascular diseases, type II diabetes, cardiac – and all-cause mortality among Danish RA patients in an observational cohort study. Methods: We identified all incident RA patients during the period of 2004 through 2014 in Denmark. HCQ initiators were compared with non-users of HCQ, stratified on rheumatoid factor positivity. Each HCQ initiator was matched to a non-HCQ initiator by their propensity score (PS). In the PS all relevant available cardiovascular drugs and comorbidities were included. All together we had 3, 742 RA patients in each group. Results: We found a significant reduction in all-cause mortality and cardiovascular related death among HCQ initiators, with a hazard ratio of 0.83 (95% confidence interval [CI] 0.71–0.97) and 0.78 (95% CI: 0.61 to 0.99), respectively. We did not find any association between HCQ use and development of type II diabetes or specific ischaemic events (myocardial infarctions and ischaemic strokes). Conclusions: The beneficial properties on survival seen with HCQ use in other inflammatory diseases seem also applicable to RA patients. These results needs confirmation in a randomised setting but justifies the use of HCQ in combination with other conventional synthetic disease-modifying antirheumatic drugs even though the effect of HCQ, per se, on RA disease activity is limited. Reference: [1] Rempenault C, Combe B, Barnetche T, Gaujoux-Viala C, Lukas C, Morel J, et al. Metabolic and cardiovascular benefits of hydroxychloroquine in patients with rheumatoid arthritis: A systematic review and meta-analysis. Ann Rheum Dis2018Jan;77(1):98–103. Disclosure of Interest: None declared